Owning Police Reform: The Path Forward for Practitioners and Researchers - Engel, Robin S. (American journal of criminal justice, 2022)
The integration of evidence-based policy into criminal justice reform - and into police reform specifically - is a daunting but necessary endeavor. In this essay, we examine police reform, including a review of the literature, which is summarized and guided by our experiences and thoughts into a broad conceptual framework for what we believe is needed to realize true change in the policing profession. This essay provides a brief review of the history of police reform and explores three primary reasons why it has failed so far: (1) the tendency to implement reactionary (i.e., knee-jerk) reforms; (2) the reliance on non-aspirational reforms; and (3) a lack of necessary evidence to guide reforms. We then provide what we believe to be the path forward - the co-ownership of evidence-based police reform by police executives and researchers. We encourage and advise police executives to be proactive, strategic, and courageous in owning reform, see greater value in being users and builders of evidence, and educate the public and their own officers. We also call on researchers to do better by creating the knowledge needed for the field and packaging it in a way that can be more easily consumed by practitioners, policymakers, and the community. We believe it is through this co-ownership that police reform efforts have the greatest potential for success.